2019
DOI: 10.1371/journal.ppat.1007796
|View full text |Cite
|
Sign up to set email alerts
|

EBV epitranscriptome reprogramming by METTL14 is critical for viral-associated tumorigenesis

Abstract: Epstein–Barr virus (EBV) is a ubiquitous oncogenic virus that induces many cancers. N6-Methyladenosine (m6A) modification regulates many cellular processes. We explored the role of m6A in EBV gene regulation and associated cancers. We have comprehensively defined m6A modification of EBV latent and lytic transcripts. Furthermore, m6A modification demonstrated a functional role in regulation of the stability of viral transcripts. The methyltransferase METTL14 was induced at the transcript and protein levels, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 42 publications
3
105
0
Order By: Relevance
“…Mechanistically, METTL14 contributes to oncogenesis through inducing m6A on the essential EBV latent antigen EBNA3C and thereby enhancing expression and stability of it. Interestingly, EBNA3C also increases expression and stability of METTL14 [54].…”
Section: Mettl14mentioning
confidence: 99%
“…Mechanistically, METTL14 contributes to oncogenesis through inducing m6A on the essential EBV latent antigen EBNA3C and thereby enhancing expression and stability of it. Interestingly, EBNA3C also increases expression and stability of METTL14 [54].…”
Section: Mettl14mentioning
confidence: 99%
“…Dynamic and reversible m 6 A regulation was reported to be involved in various physiological and pathological processes including stem cell differentiation, cardiac homeostasis, adipogenesis, neuronal disorders, and spermatogenesis [15][16][17][18][19] . Recent years, compelling evidence has revealed that m 6 A modification plays an important role in the tumorigenesis of various cancers [20][21][22][23][24] . For example, METTL3 was reported to play key role in the progression of colorectal carcinoma 25 , bladder cancer 26,27 , gastric cancer 28 , and pancreatic cancer 29 .…”
Section: Introductionmentioning
confidence: 99%
“…A research conducted by Zhang et al suggested that m6A modification was positively correlated with TMB/MSI status, and might be involved in immune responses of gastric cancer [ 61 ]. EBV-associated tumorigenesis has also been confirmed to require epitranscriptome reprogramming by METTL14 [ 82 ]. Thereby exploration of novel immunotherapy strategies targeting m6A is worth in-depth.…”
Section: Conclusion and Future Prospectusmentioning
confidence: 99%